ENGARUH EKSTRAK PATIKAN KEBO (EUPHORBIA HIRTA L.) TERHADAP HITUNG EOSINOFIL DARAH TEPI PADA MENCIT MODEL ASMA ALERGI - Heri Prasetyo, Diding; Putranto, R.P. Andri; Martini, Martini; Sarsono, Sarsono (Lembaga Penelitian Universitas YARSI, 2008)
Asthma is characterized by both chronic inflammation and remodeling of the airways. Eosinophils may contribute to inflammation associated with bronchial asthma by causing tissue damage and subsequently organ dysfunction, but also by the generation of cytokines and lipid mediators. It was reported in previous studies that pharmacological activities were identified in various compounds extracted fromEuphorbia hirta L. such as antiinflammatory,histamine inhibitor, lipoxygenase inhibitor, anti-allergic and cyclooxygenase inhibitor. This study was aimed to determine the effect of E. hirtaextract onperipheral blood eosinophils count in mice model of allergic asthma. MaleBalb/C mice were sensitized and challenged intraperitoneally (i.p) with ovalbumin(OVA). Mice were immunized i.p. on days 1 and 14 with 2.5 mgof OVA adsorbed to 7.75ml of Aluminium hydroxide gel. OVA challenges (10 mgOVA in l ml of PBS) were administered aerosolly on days 21, 23, 25 and 27, andperipheral blood eosinophilscount was determinedon day 28.A one-way analysis of variance (ANOVA) with LSDpost hocanalysis was used to determine significant differences. Results were expressed as mean+SEM, and values of p 0.05wereconsidered statistically significant. The results showed thatperipheral blood eosinophilscountin the OVA group was51.0+10.4cells/mm E. hirtaextract dose 500 mg/BW/day was30.2+6.3cells/mm3,E. hirtaextract dose 1,000 mg/BW/day was 30.4+6.0cells/mm and antihistamine group was32.2+8.6cells/mm respectively, whilecontrol mice showed46.6-8.8 cells/mm3. It was concluded that E. hirta extract could minimizeperipheralblood eosinophilscount.